URGENSI IZIN USAHA PETERNAKAN SEBAGAI KEWAJIBAN HUKUM DAN DASAR LEGALITAS USAHA PETERNAKAN DI INDONESIA - Lananda, Ardelia; Mulyadi, M. Budi (The Juris, 2025)
Livestock business licensing is one of the important instruments in the Indonesian legal system that not only functions as a form of compliance with the law, but also as a legal basis to ensure the feasibility, security, and sustainability of livestock businesses. In addition, this livestock business license is also a fundamental aspect in the implementation of legitimate and responsible livestock business activities in Indonesia. The purpose of this study is to examine in more depth the regulations or legal arrangements regarding livestock business licensing in the legal system in Indonesia, analyze the urgency of livestock business licensing as a legal obligation and legal basis in organizing livestock businesses in Indonesia, and identify legal implications for livestock business actors who do not fulfill licensing obligations in accordance with the provisions of the applicable law in Indonesia. The method used in this study is the normative legal research method. This research method is carried out by examining problems and processing data obtained from legal regulations in accordance with existing regulations and rules or norms as the basis for research. The results of the study show that the existence of business permits in the livestock sector not only provides legal certainty, but also functions as a preventive mechanism against various legal and social risks, so that strengthening an effective and efficient licensing system is urgently needed to realize legal, sustainable, and public protection-oriented livestock business governance.